New Constraints on Early Mars Weathering Conditions From an Experimental Approach on Crust Simulants. Issue 7 (10th July 2019) - Baron, F.; Gaudin, A.; Lorand, J.‐P.; Mangold, N.
Abstract: A denser CO2 atmosphere and higher temperatures than present‐day conditions are frequently invoked as prevailing conditions for the formation of some ancient hydrous mineralogical associations present at the surface of Mars. The environmental conditions are of particular interest to better understand and constrain the weathering processes of the early Martian crust. For this purpose, 6‐month‐long batch weathering experiments on Martian crust simulants and individual Martian mineral analogs were performed at low temperature (45 °C) under a dense CO2 atmosphere (1 atm). Constraints on the weathering conditions are deduced from the solution properties and thermodynamic calculations, as well as mass balance calculations. Experimental solutions vary from mildly acidic to near neutral (4.75–6.48 pH). The Eh‐pH conditions (Eh from 0.189–0.416 V/standard hydrogen electrode) suggest favorable conditions for the formation of ferric minerals despite an anoxic CO2 atmosphere. The chemical weathering appears to be 4 times more intense for Martian simulants under a CO2 atmosphere than under Earth ambient air. The weathering trend under a CO2 atmosphere involves leaching of alkali and alkaline earth elements (Mg, Ca, Na, and K) and Si and enrichments of the solid phases in Al, Fe, and to a lesser extent Si compared to the initial chemical composition of the starting minerals. This geochemical partitioning between solution and solids resembles those deduced from weathering profiles on Earth. Our results strongly support the idea that carbonates could not have extensively formed at the surface of early Mars despite a dense CO2 atmosphere. Plain Language Summary: Mars orbital and landed missions have provided mineralogical, morphological, and field evidence for liquid water at the surface approximately 3.5 billion years ago. The chemical and mineralogical composition of the Martian rocks have potentially been modified by interaction with this liquid water. The purpose of our study is to use laboratory experiments to constrain the physicochemical conditions of water resulting from the chemical weathering of Martian crust simulants under an atmosphere composed of carbon dioxide, as is the case for Mars. The water in contact with simulants is mildly acidic. The partitioning of chemical elements between the solution and minerals is similar to what is observed on Earth, but weathering is more intense. Despite that Mars had a primitive CO2 ‐dense atmosphere, the conditions were not favorable to the extensive formation of carbonate at the surface. Key Points: Chemical weathering in mildly acidic conditions under a CO2 atmosphere yielded leaching of alkali and alkaline earth elements Mass balance calculations indicated Al, Fe, and Si enrichment in the weathering products Our results imply unsuitable conditions for carbonate formation despite CO2 in the Martian atmosphere